A feasibility study of the implementation of total quality management based on soft factor - Arash Shahin; Reza Dabestani (Journal of Industrial Engineering and Management (JIEM), 2011)
Purpose: The aim of this paper is to examine the feasibility of implementing TQM based on soft factors, which can influence the successful implementation of TQM. Design/methodology/approach: A framework has been developed for the TQM soft factors based on literature review and respectively, questionnaires which are directly related to the addressed factors have been designed and distributed to the employees of an engineering service company as the main enablers of improving the effectiveness of TQM. Findings: The findings imply that committed leadership, closer customer relationship, benchmarking and process improvement have the most correlations amongst the TQM soft factors. Training is the only factor which is not correlated to other soft factors. Leadership has also the highest value among the soft factors. Research limitations/implications: The proposed framework is costly and time consuming due to the large number of questions it holds. In this study, it is assumed that sub factors have the same importance. But there is a possibility in which these subdivisions do not have the same relative importance weight. The study is also limited to one company and therefore, the findings should not be generalized. Practical implications: The proposed TQM soft factors framework can be useful for those organizations which consider TQM as an integrated quality management system as the major foundation for achievement of competitive advantage. Originality/value: A comprehensive framework for TQM soft factors has been presented since it involves almost all of the soft factors addressed in the literature.
Keywords: 650; total quality management; soft factors; framework; feasibility